Penggunaan Media Video & Gambar Dalam Pembelajaraan IPAS Pada Siswa Kelas 4 SDN 1 Wonoboyo - Wahyu, Dwi (Pendidikan Dasar dan Manajemen Pendidikan, 2023)
This research aims to explore the use of video and image media in learning Natural Sciences (IPAs) for grade 4 students at SDN 1 Wonoboyo. Visual media has become an important component in modern education, and this research investigates how the use of this media can influence students' understanding and motivation in learning sciences. The research results show that the use of video and image media in science learning positively influences students' understanding of the concepts being taught. Students also show higher interest and motivation to learn when visual media is used. Even though it requires more intensive preparation for teachers, the use of visual media is considered effective in explaining complex science concepts. This research provides insight into the importance of using visual media in improving the quality of science learning at the elementary level and suggests that teachers and schools continue to develop their skills in integrating this media in the curriculum. Video and image media have great potential in motivating students and facilitating better understanding of science material, so they can be effective tools in improving education at the elementary level.